2014
DOI: 10.5430/jst.v4n2p25
|View full text |Cite
|
Sign up to set email alerts
|

Systemic therapy for bladder cancer – a medical oncologist’s perspective

Abstract: Advanced bladder cancer, both muscle-invasive localized disease and metastatic disease, is managed with systemic chemotherapy. Cisplatin-based multi-agent chemotherapy remains the cornerstone for systemic therapy. MVAC (methotrexate-vinblastine-doxorubicin-cisplatin) has been most rigorously studied, both neoadjuvantly and for palliation of metastatic disease. For metastatic disease, cisplatin-gemcitabine (GC) has compared favorably to MVAC due to improved tolerability with similar efficacy. GC has been adopte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…Although most patients with NMIBC generally have favorable outcomes, local therapy with chemotherapy mainly based on mitomycin C often requires repeated treatments [47]. Interestingly, we found that EA enhanced the antiproliferative effects of mitomycin C. These data suggest that also a less aggressive disease might benefit from local or systemic therapy with this compound, possibly reducing the frequency of administration of the chemotherapeutic agent.…”
Section: Discussionmentioning
confidence: 55%
“…Although most patients with NMIBC generally have favorable outcomes, local therapy with chemotherapy mainly based on mitomycin C often requires repeated treatments [47]. Interestingly, we found that EA enhanced the antiproliferative effects of mitomycin C. These data suggest that also a less aggressive disease might benefit from local or systemic therapy with this compound, possibly reducing the frequency of administration of the chemotherapeutic agent.…”
Section: Discussionmentioning
confidence: 55%
“…The overall survival rates are 7% for patients with visceral metastases and 21% for patients without visceral metastases . The evolution of successful targeted therapies for patients with non‐small cell lung cancer and other solid tumors has contrasted significantly with the lack of such approaches reaching regulatory approvals or late‐stage clinical trials for UCB . The purpose of the current study was to expand and validate the identification of CRGAs in a large series of 295 patients with UCB and demonstrate the impact of targeted therapies in selected patients in whom genomically driven treatment was undertaken.…”
Section: Discussionmentioning
confidence: 97%
“…These successes have led to more rapid drug development and regulatory approvals for targeted therapies for these and other solid tumors and hematolymphoid malignancies . However, for patients with locoregionally advanced and metastatic UCB, targeted therapies have not been approved and patients have limited therapeutic options because chemoresistance to the standard anticancer therapies develops . Thus, there recently has been a growing interest in the development of targeted therapy for UCB .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its mechanisms of action include the induction of apoptosis of tumor cells by intercalating into their DNA to inhibit its transcription and initiate a DNA damage response (5). DOX-based chemotherapy is used against a wide range of cancer types, including ovarian (6), breast (7) and bladder cancer (8) as well as HCC (9). However, the clinical application of DOX is limited due to cardiac toxicity and drug resistance (10).…”
Section: Introductionmentioning
confidence: 99%